PERLINDUNGAN KONSUMEN TERHADAP KLAUSULA EKSONERASI DALAM PERJANJIAN BAKU PERUSAHAAN JASA PENGIRIMAN BARANG - Ariesta Dwicahyani Putri, Dewa Ayu; Sekar, I Dewa Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013, 2013)
This paper shall be entitled as “Consumer Protection Towards ExonerationClause In Freight Forwading Services Agreements By Companies". This paper shallapply normative legal research method combined with statutory approach. Agreementwhich uses exonerating clause had been widely spread throughout public usage due toits time and financial efficiency. As it further developed, the usage of such related termhad implied certain incompliance of requirements which latter exerted disadvantages tocertain party and otherwise. This paper shall illustrate regarding exonerating clauseused by agreements in freight forwarding services by companies from the perspective ofconsumer protection based on its respective Act.
Keywords: Protection, Consumer, Exoneration, Standart Contract